Flipping an IELTS Writing Course: Investigating its impacts on students’ performance and their attitudes - Safrul Muluk; Zamzami Zainuddin; Syarifah Dahliana (Universitas Syiah Kuala, 2022)
The technology-enhanced instructional approach has been proven to stimulate active learning and advance the teaching-learning process. The flipped classroom (FC) instructional method, an instructional technology part of blended learning, has gained remarkable popularity in recent years due to its promising and positive impacts on different aspects of students’ learning process (motivation, engagement, academic performance, independent learning). In the current study, an explanatory mixed-method approach was employed to investigate the implementation of the flipped pedagogical approach in a government-funded IELTS preparation course in Indonesia, particularly in the writing section of the course. It examined the impacts of this instructional technology method on learners’ writing performance and explored their learning attitudes and experiences. A number of 25 participants from various professional backgrounds aspiring to pursue master’s and doctoral degrees who were recruited based on their previous TOEFL or IELTS scores participated in this study. The findings of this study showed that the learners had a positive attitude toward the flipped instruction method, and their writing test achievement significantly improved as reflected in the official IELTS test scores. Method flexibility, independent learning, and collaborative and active learning were factors that emerged in the interviews that were considered the important determinants of the participants’ IELTS writing improvements.